Can Europe survive? : the story of a continent in a fractured world - Marsh, David, 1952- (New Haven ; London : Yale University Press, 2025)
A bold new account of Europe’s plight as it faces political fracture, economic stagnation and external challenges from the U.S., China and Russia Today, Europe finds itself in a fast-changing, polarised world dominated by Chinese-American rivalry. The European Union and its surrounding nonmember states, despite initial successes after the fall of the Berlin Wall, have failed to implement a strategy for success in the twenty-first century. Britain’s exit from the Union has weakened both sides, and Russia’s invasion of Ukraine has thrown these shortcomings into sharp relief. How should states across the continent position themselves in the decades to come? Drawing on unpublished archives and interviews with over 150 leading figures, David Marsh investigates Europe’s present crisis, from the march of populism, Franco-German malaise, and the breakdown of relations with Putin’s Russia. Fault lines are emerging in the monetary union, while the fight against climate change has impacted growth. Facing its gravest test since the Second World War, Europe must find fresh reserves of resilience—and seek out renewed international partnerships to ensure success.
Publikace přináší analytický a kritický pohled na současné postavení Evropy v geopoliticky roztříštěném a rychle se měnícím světě. Autor zkoumá politické, ekonomické a institucionální slabiny Evropské unie i širšího evropského prostoru v kontextu rostoucí rivality mezi Spojenými státy a Čínou, ruské agrese vůči Ukrajině a vnitřních rozporů evropské integrace. Text se věnuje tématům populismu, oslabení francouzsko-německého partnerství, problémům měnové unie, dopadům klimatické politiky na hospodářský růst i důsledkům brexitu. Na základě archivního výzkumu a rozhovorů s klíčovými politickými a ekonomickými aktéry autor analyzuje možné scénáře dalšího vývoje a hledá zdroje nové evropské odolnosti a mezinárodní spolupráce.
Obsahuje bibliografii, bibliografické odkazy a rejstřík
Keywords: Evropská unie; 21. století; mezinárodní vztahy; geopolitika; evropská dezintegrace; politiky Evropské unie; mezinárodní konflikty; Evropa; monografie; 21st century; international relations; geopolitics; European disintegration; European policies; international conflicts; Europe; monographs